The Elephant in the Room: Race and STEM Diversity. (5th February 2020) - Miriti, Maria N
Abstract: Despite considerable efforts to enhance participation of underrepresented demographics, participation of scholars of color in STEM remains stagnant. In contrast to other academic disciplines, the experiences of STEM scholars of color are relatively unvoiced, which hinders examination of the factors that reduce participation and retention. Social science and education research reveal the importance of intersectional strategies to address institutional and cultural practices that reduce diverse participation. Institutional change requires the support of the STEM workforce. I summarize important issues that influence recruitment and retention and offer strategies that can improve recruitment and retention of faculty of color. Broad awareness among STEM practitioners of the relationship between race and the biases that reduce recruitment and retention of underrepresented scholars can support STEM diversity initiatives.